Effect of Different Dilutions of Milt in Physiological 0.9% NaCl on Fertilization Rate, and Hatching Rate of the Lukas Fish, Puntius bramoides (Valenciennes, 1842) - Abinawanto .; P. Pratiwi; S. Yimastria (New Visions in Science and Technology Vol. 7, 2021)
The Lukas fish, Puntius bramoides is one of the local fish and had has an economic value. The objective of study was to evaluate the effect of different dilutions of milt in 0.9% NaCl on the fertilization rate and hatching rate. Milt and eggs were collected by stripping after injecting fish by GnRH analogue. The ratio of milt and diluents was 1:9. The experimental treatment consisted of four groups, namely: A (normal/control, without dilution), B (10 times dilution), C (100 times dilution), and D (1000 times dilution). Eggs were fertilized manually, and were calculated the percentage of fertility and hatching rate. The results showed that 1000 times dilutions tend to show the highest percentage of fertility and hatching rate (78.92 ± 1.81)% and (72.33 ± 4.56)%, respectively, based on the ANOVA test.